1997
DOI: 10.1007/bf02632936
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the treatment of natural haemosporidia infections by total alkaloid ofPeganum harmala L. in cattle

Abstract: Eighty two cattle naturally infected with haemosporidians were treated with total alkaloid hydrochloride of Peganum harmale L. (0.5 mg/kg/day). Fifty eight cases with Theileria sergenti showed a cure rate of 86%; thirteen cases with Theileria annulata showed a cure rate of 85%; eight cattle infected with Babesia bigemina showed a cure rate of 88% and three cases of Anaplasma marginale were completely cured. The results suggested that the curative effect of total alkaloid of P. harmale was better than that of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
4
3
0
Order By: Relevance
“…The reasons for this apparent discrepancy in the success rate of the treatment in our experiment and that of Mirzaie & Shaddel (2004) could be the different environmental conditions in which their sheep were maintained, the small numbers of sheep they used and the fact that the infection was experimentally induced. Our results are in agreement with that of other experiments in which the alkaloids of P. harmala were used for the treatment of tropical theileriosis in cattle (Agaev, Mirzabekov, Gumbatov & Mirzabekov 1977;Vecherkin, Puzii, Romakhov & Tribunskii 1977;Charyev & Khudaiberdyev 1978;Levchenko 1978Levchenko , 1979Puzii, Vetchorkin, Romakhov & Vecherkin 1979;Puzii, Vecherkin, Toptaev, Tsyganova & Duisheev 1982;Fan et al 1997;Hu et al 1997).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reasons for this apparent discrepancy in the success rate of the treatment in our experiment and that of Mirzaie & Shaddel (2004) could be the different environmental conditions in which their sheep were maintained, the small numbers of sheep they used and the fact that the infection was experimentally induced. Our results are in agreement with that of other experiments in which the alkaloids of P. harmala were used for the treatment of tropical theileriosis in cattle (Agaev, Mirzabekov, Gumbatov & Mirzabekov 1977;Vecherkin, Puzii, Romakhov & Tribunskii 1977;Charyev & Khudaiberdyev 1978;Levchenko 1978Levchenko , 1979Puzii, Vetchorkin, Romakhov & Vecherkin 1979;Puzii, Vecherkin, Toptaev, Tsyganova & Duisheev 1982;Fan et al 1997;Hu et al 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Tests have shown that these two compounds are effective (Hooshmand-Rad 1989) but they are not easily and quickly eliminated from the body of animals (McHardy, Wekesa, Hudson & Randall 1985) which can constitute a public health hazard if milk and meat of treated animals are consumed by humans. The therapeutic effect of the alka loids of the plant Peganum harmala has been investigated for the treatment of tropical theileriosis in cattle which is caused by Theileria annulata and it was shown that they are effective (Fan, Liang, Men, Gao, Li, Zhao, Hu, Dang, Zhang, Preston & Yin 1997;Hu, Fan, Liang, Zhao, Dang, Gao, Dong, Preston & Yin 1997) In addition, it has been shown that these alkaloids, when inoculated intramuscularly do not infiltrate the muscular tissue surrounding the inoculation site but are also rapidly eliminated from the body (Puzii & Serov 1983). The objective of this study was to study the effect of total alkaloids of P. harmala when used for the treatment of naturally infected cases of ovine malignant theileriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with those of other experiments in which the alkaloids of P. harmala were used for the treatment of tropical theileriosis in cattle (Agaeve, Mirzabekov, Gumbatov & Mirzabekov 1977;Vecherkin, Puzii, Romakhov & Tribunskii 1977;Charyev & Khudaiberdyev 1978;Levchenko 1978Levchenko , 1979Puzii, Vetchorkin, Romakhov & Vecherkin 1979;Puzii, Vecherkin, Toptaev, Tsyganova & Duisheev 1982;Fan et al 1997;Hu et al 1997). The pathologic findings of the lambs in Group B confirmed that they had died of malignant theileriosis (Radostits, Gay, Blood & Hinchcliff 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Among the several alkaloids, harmaline (harmidine, C 13 H 14 N 2 O) has been found to be the major active alkaloid which can cause cell death due to non-specific membrane damage (Budavari & O'Neil 1996;Lala, Pramanick, Mukhopadhyay, Bandyopadhyay & Basu 2004). The therapeutic effect of the alkaloids of the plant Peganum harmala has been investigated for the treatment of tropical theileriosis in cattle, which is caused by Theileria annulata, and in sheep naturally infected with Theileria hirci; it was shown that they are effective (Fan, Liang, Men, Gao, Li, Zhao, Hu, Dang, Zhang, Preston & Yin 1997;Hu, Fan, Liang, Zhao, Dang, Gao, Dong, Preston & Yin 1997;Mirzaie dehaghi 2006). In addition, it has been shown that these alkaloids, when inoculated intramuscularly, do not infiltrate the muscular tissue surrounding the inoculation site but are rapidly eliminated from the body (Puzii & Serov 1983).…”
Section: Peganum Harmala Lmentioning
confidence: 99%
“…The alkaloids in the seed extract have been utilized to control hemosporidian infection in naturally and experimentally infected cattle Hu et al, 1997). Until now, the effect of Peganum harmala seed extract was only studied in mammalian models, and its therapeutic doses have been reported to be safe for rodents (Lamchouri et al, 2002).…”
Section: Discussionmentioning
confidence: 99%